PENGARUH PRAKTIK KERJA LAPANGAN DAN UJI KOMPETENSI KEAHLIAN TERHADAP KESIAPAN KERJA SISWA KELAS XII SMK NEGERI 1 MERANGIN - Dinda Aulia; Muhamad Arif Liputo; Dwi Rayana Siregar (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the influence of Field Work Practice (Praktik Kerja Lapangan/PKL) and the Vocational Competency Test (Uji Kompetensi Keahlian/UKK) on the work readiness of twelfth-grade students at SMK Negeri 1 Merangin. The study employed a quantitative approach using an ex post facto research design. The sample consisted of 97 students selected from three vocational programs. Data were collected through questionnaires and students’ competency scores, while data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics 26. The results revealed that Field Work Practice has a positive and significant effect on students’ work readiness (t = 6.120; Sig. = 0.000 < 0.05). Likewise, the Vocational Competency Test has a positive and significant effect on students’ work readiness (t = 6.835; Sig. = 0.000 < 0.05). Simultaneously, PKL and UKK significantly affect students’ work readiness (F = 47.397; Sig. = 0.000 < 0.05). The coefficient of determination (R²) of 0.502 indicates that both variables explain 50.2% of the variation in students’ work readiness. The novelty of this study lies in examining the simultaneous effect of Field Work Practice and the Vocational Competency Test on the work readiness of students at SMK Negeri 1 Merangin as an effort to support the development of graduates who are better prepared to enter the workforce.